2015
DOI: 10.1055/s-0035-1547614
|View full text |Cite
|
Sign up to set email alerts
|

Genomic landscape of pancreatic neuroendocrine tumors

Abstract: AIM:To investigate the prognostic role of genomic stability and copy number alterations (CNAs) pancreatic neuroendocrine tumors (PanNETs). METHODS:A high-resolution array-based comparative genomic hybridization approach was utilized in order to investigate and quantify chromosomal aberrations in a panel of 37 primary PanNET and 11 metastatic samples. DNA samples were extracted from formalinfixed and paraffin-embedded tumor specimen. Genomic findings were correlated with histopathological and immunohistochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Various studies have identified non-mutational biomarkers associated with tumor progression/metastasis that could potentially assist with management. Copy-number alterations at certain chromosomal loci, such as 6p22.2-p22.1, 8q24.3, 9q34.11, and 17p13.1 have been associated with poorer prognosis ( 65 ). This is an important area of ongoing research, though the prognostic implications of other copy-number alterations and chromosomal translocations are poorly defined at this time.…”
Section: Molecular Mechanisms and Prognosis In Pnetsmentioning
confidence: 99%
“…Various studies have identified non-mutational biomarkers associated with tumor progression/metastasis that could potentially assist with management. Copy-number alterations at certain chromosomal loci, such as 6p22.2-p22.1, 8q24.3, 9q34.11, and 17p13.1 have been associated with poorer prognosis ( 65 ). This is an important area of ongoing research, though the prognostic implications of other copy-number alterations and chromosomal translocations are poorly defined at this time.…”
Section: Molecular Mechanisms and Prognosis In Pnetsmentioning
confidence: 99%